2010
DOI: 10.1590/s0103-90162010000600012
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic efficiency and genetic characteristics of Bradyrhizobium sp. strain UFSM LA 1.3 isolated from Lupinus albescens (H. et Arn)

Abstract: Legume species belonging to the genus Lupinus are annual herb plants. The majority of them are indigenous to the Americas. They are known for nitrogen-fixing symbioses with soil bacteria collectively called rhizobia. The aim of this study was to characterize a rhizobium strain isolated from Lupinus albescens using phenotypic, symbiotic and molecular approaches. Strain UFSM LA 1.3 was tested in vitro according to several parameters: colony size, color and growing rate; acid or alkaline reaction in yeast mannito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
0
3
0
4
Order By: Relevance
“…& Arn. grows on coastal sand dunes and riverine sand banks in southern Brazil, Argentina, and Uruguay (Stroschein et al, 2010). In eastern North America, the four unifoliate lupines and, in eastern South America, lupines of the unifoliate group grow on very sandy nutrient‐poor soils (e.g., pine flatwoods in southeastern USA and South American cerrado savannas) that are also subject to frequent fires (Eastwood et al, 2008).…”
Section: Soil‐type Adaptationsmentioning
confidence: 99%
“…& Arn. grows on coastal sand dunes and riverine sand banks in southern Brazil, Argentina, and Uruguay (Stroschein et al, 2010). In eastern North America, the four unifoliate lupines and, in eastern South America, lupines of the unifoliate group grow on very sandy nutrient‐poor soils (e.g., pine flatwoods in southeastern USA and South American cerrado savannas) that are also subject to frequent fires (Eastwood et al, 2008).…”
Section: Soil‐type Adaptationsmentioning
confidence: 99%
“…Adding the genome of the reference strain B. japonicum USDA 6 to the comparison ( Figure 3B ), genomes from AS23 and NAS80 resulted in a similar amount of genes shared with the reference genome (5,129 and 5,134, respectively), while the genome of isolate NAS96 shared 4,717 genes with the genome of USDA 6. Similarities among selected genes from Bradyrhizobium strains isolated from root nodules of L. albescens with the respective genes from B. japonicum species had already been observed by Stroschein et al (2010) and Granada et al (2015) . However, both works suggested that those bacterial isolates probably constituted new Bradyrhizobium species.…”
mentioning
confidence: 71%
“…O gênero Rhizobium, composto por microrganismos genericamente identificados como rizóbios, bactérias gram negativas, é geralmente relacionado a bactérias fixadoras de nitrogênio formadoras de nódulos em leguminosas (Stroschein, 2010). Singh et al (2015) isolaram Rhizobium radiobacter em milho, e também identificaram a capacidade de promoção de crescimento dessa bactéria.…”
Section: Resultsunclassified